Economic Security and its Assessment in Accounting Information System - Larisa K. Nikandrova (Учёт. Анализ. Аудит)
The specifics of the market relations cause the emergence of enterprise risks which, this way or the other, influence the economic security of economic entities. The economic nature of the category “economic security of an economic entity” represents a combination of the economic and legal conditions which provide steady functioning of enterprise structures in the long run. The essence of economic security comprises the elimination of risks such as the threat of decrease in business efficiency, legal matters, and the expediency of use of labor, financial, production and land resources with the help of lawful and effective methods. Analysis and diagnostics of financial and economic activity of economic entities are one of the main conditions that ensure economic security. The reliability of the results of the analysis and diagnostics of the condition of an enterprise depends generally on the reliability of the information used as the analytical base. It, in turn, is defined by the reliability of accounting system of the organization.